Amṡāl in Hadīṡ: Literature Review on The Work of Ibnu Khalād al Rāmahurmuzī - Umi Aflaha -; Nur Aini (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
Amṡāl (simile) is part of the Arabic style containing short messages in terms of a sentence but wide in meaning. This paper examines the book by Ibn Khalād al Rāmahurmuzī, which contains amṡāl in hadith. This research used a descriptive-analytical method and employed a book analyses study approach in order to find out: (1) The characteristics, methods, and sources of the hadiths were used. (2) The author's method in explaining the hadiths of amṡāl. (3) The weaknesses and the strengths of the book. This research found that the themes of hadith collected in each chapter are based on the aspects of the theme content and the language style used, namely: at-tasybīh and al-kināyah. Second, this book's method of narrating the hadith is the simā' method. The hadith used comes from the hadith expert priests. Third, in explaining the meaning of amṡāl, the author quotes the opinion of 'ulama and Arabic poetry. Fourth, the book's strengths are the explanation from the author regarding the purpose of the amṡāl in hadith. As for the weakness of the book, the author ignores the quality of the hadith, so there is no information whether the hadith is ṣahīh, ḥasan, or ḍa'īf.